ANALISIS ANGGARAN PENJUALAN SEBAGAI ALAT PERENCANAAN LABA PADA PT WAHANA PERSADA KARTON PALEMBANG - Dessi Kurniawati; Jamiyla Jamiyla; Trie Sartika Pratiwi (Jurnal Ilmiah Ekonomi Global Masa Kini)
This thesis is entitled "Analysis of Sales Budget as Planning Tool of Profit in PT Wahana Persada Karton Palembang". PT Wahana Persada Karton Palembang is a company engaged in the sale of boxes. To obtain the data, the author used data collection methods such as interviews, documentation and library research related to the problems that occured. Based on the results of the analysis conducted, the company implemented a top-down system (Authoritarian) in performing the procedure of preparing the salesman budget from the data of the previous year's salesman realization, so the company has not made a good budget preparation as a tool of profit planning. The author proposed recommendations to companies to consider using forecasting sales the quadratic method of preparation of the sales budget. By using this method the company can see how much sales targets to be achieved in the period to come and to know the factors causing  the difference between sales budget with its realization.Keywords: Forecasting  Sales, Sales Budgeting, Profit Planning